2015
DOI: 10.1371/journal.pone.0132169
|View full text |Cite
|
Sign up to set email alerts
|

Iconic Meaning in Music: An Event-Related Potential Study

Abstract: Although there has been extensive research on the processing of the emotional meaning of music, little is known about other aspects of listeners’ experience of music. The present study investigated the neural correlates of the iconic meaning of music. Event-related potentials (ERP) were recorded while a group of 20 music majors and a group of 20 non-music majors performed a lexical decision task in the context of implicit musical iconic meaning priming. ERP analysis revealed a significant N400 effect of congru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies with NH participants have demonstrated that music can prime meaningful concepts 14 34 35 37 . To be able to make applicable comparisons, we therefore drew on the mentioned stimulus set by Koelsch et al which had already been validated in a NH group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with NH participants have demonstrated that music can prime meaningful concepts 14 34 35 37 . To be able to make applicable comparisons, we therefore drew on the mentioned stimulus set by Koelsch et al which had already been validated in a NH group.…”
Section: Discussionmentioning
confidence: 99%
“…See Supplementary Table S4 for a description of CIU participant demographics. Sample size justification, especially for the ERP experiment, is given by studies using the same procedures 14 34 37 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation